Review peptides and proteins wired into the electrical circuits: An SPM‐based approach1. Issue 1 (19th January 2013) - Sek, Slawomir; Maran, Flavio; Toniolo, Claudio
Abstract Development of molecular scale electronics stimulates the search for new functional materials and compounds. One of the promising directions of further growth within this field is bioelectronics, which assumes the use of electron transfer (ET)‐mediating properties of bio‐related compounds. Because of the structural and functional versatility, peptides and proteins are particularly well suited to perform as single‐molecule‐based elements of circuits or sensing devices. In this review, it is demonstrated that purposely designed systems such as molecular junctions are excellent platforms for the studies of ET properties of peptides and proteins at nanoscale level. Using experimental approach based on scanning probe microscopy, individual molecules can be directly wired between two metallic contacts, and their conductance can be determined. ET behavior of the peptides and proteins can be analyzed in terms of their applicability as molecular wires, switches, diodes and elements of sensing devices. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 71–81, 2013.